Análisis Multitemporal Del Crecimiento Urbano De La Ciudad De Bogotá D.C. Para El Periodo 2000 – 2018 (2025)
This study presents a multitemporal analysis to assess the urban growth of Bogotá D.C. between 2000 and 2018 by identifying its urban coverage in the years 2000, 2010, and 2018, and quantifying the growth of the built area. The methodology utilizes satellite images from Landsat 5, 7, and 8, processed through supervised classification under the CORINE Land Cover methodology. To ensure accuracy, atmospheric and radiometric corrections were applied, and the accuracy was validated using the Kappa coefficient, achieving a high agreement in the results.